Extraction and wound healing potential of Nerium Indicum M, Artocarpus Heterophyllus Lam, Murraya Koenigii L, Punica Granatum L on albino rats using burn wound model - Shukla, Renuka; Kashaw, Varsha (Journal of Drug Delivery and Therapeutics, 2019)
Objective: The objective of present work was to extract the active constituents and evaluate the wound healing potential of Nerium indicum, Artocarpus heterophyllus, Murraya koenigii, Punica granatum on albino rats using burn wound model. Poly-herbal ointment and gel formulation was developed and compare with the extract of all plants. These plants has shown anti-asthmatic, anti-diabetic, anti-inflammatory, anti-microbial, anti-leukemic, anti-mycobacterial, antibacterial, antioxidant, antiulcer, antiviral, anticancer, antimalarial, anti-inflammatory and wound healing properties. Materials and Methods: Solvent extraction method has been utilized for the separation of the active constituents of interest by using 70% ethanol as a solvent. Poly-herbal ointment and gel formulations has been prepared by mixing the extract of Nerium Indicum, Artocarpus heterophyllus, Murraya koenigii and Punica granatum in different ratio with the ointment base (10-15%) contains PEG and for gel formulation Carbapol-940 base (10-15%). Burn wound model of albino rats has been utilized for the assessment of wound healing potential of the plant extract as well as developed formulations. Results and Conclusion: The studies on burn wound healing model reveals that F2 poly-herbal ointment formulation show better burn wound healing potential in comparison to all other formulations, F-1 ointment formulation as well as extracts of all plants. There was no mortality observed in the tenure of study. Discussion: These data has indicated that ointment and gel poly-herbal formulation of Nerium Indicum, Artocarpus Heterophyllus, Murraya Koenigii and Punica Granatum has been utilized for wound healing purpose and it is safer for topical application. No toxicity and mortality has been observed during the experimental tenure. Keywords: Wound healing, Nerium indicum, Murraya koenigii, Punica granatum, Artocarpus heterophyllus, burn wound model.